2012
DOI: 10.4028/www.scientific.net/amr.443-444.671
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Inlet Temperature of Methanol Synthesis Reactor of LURGI Type

Abstract: This paper presents an optimization study of inlet temperature of methanol synthesis reactor of LURGI type by using commercial simulator Aspen Plus and Aspen Energy Analyzer. The optimization routine is coupled to a steady-state model of the methanol synthesis reactor. By investigating the influences on methanol production and heat exchanger network synthesis, the inlet temperature of the reactor is optimized. when the inlet temperature is 230°C, the economic benefits of the methanol plant is maximized which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The Campos model, similar to the Bussche model, also considers the source of carbon from CO 2 . The four kinetic models were simulated and the validity of the simulations was tested on an industrial Lurgi-type reactor, located at the Tuha Oilfield Company. , The results of simulations along with the industrial data are demonstrated in Figure , and for the sake of clarity, the percentage errors are provided in Table . It can be seen that the Bussche model compared to the Graaf model is in a better agreement with the industrial plant data.…”
Section: Simulation Of Reaction Subunitsmentioning
confidence: 99%
“…The Campos model, similar to the Bussche model, also considers the source of carbon from CO 2 . The four kinetic models were simulated and the validity of the simulations was tested on an industrial Lurgi-type reactor, located at the Tuha Oilfield Company. , The results of simulations along with the industrial data are demonstrated in Figure , and for the sake of clarity, the percentage errors are provided in Table . It can be seen that the Bussche model compared to the Graaf model is in a better agreement with the industrial plant data.…”
Section: Simulation Of Reaction Subunitsmentioning
confidence: 99%
“…Two routes of methanol synthesis can be found in public literature, i.e., (1) CO 2 shifts to CO through RWGS, and then CO convert into CH 3 OH; (2) CO 2 convert into CH 3 OH through an intermediate HCOO [ 3 ]. Undergo the experimental research of many years, Skrzypel et al [ 54 ] and Vanden Bussche and Froment [ 55 ] confirmed that CO 2 is the main source of methanol synthesis, and CO and CO 2 can mutual converts through the RWGS reaction [ 2 , 9 ]. Two reactions occurring in the reactor are as follows [ 9 , 36 , 44 ]: where is the enthalpy of reaction .…”
Section: Reactor Model and System Descriptionmentioning
confidence: 99%
“…In this paper, the kinetic model established by Vanden Bussche and Froment [ 44 ] is selected and utilized, since this kinetic model is based on the ICI 51-2 Cu/ZnO/Al 2 O 3 catalyst, which is applied widely in chemical industries, such as the LURGI type methanol synthesis reactor [ 9 ]. Another reason is that the kinetic model proposed by Reference [ 44 ] has been checked by experiments of lab-scale [ 44 , 55 ] and commercial-scale [ 9 ], what is more, the kinetic model has a wider application range. The temperature varies between 180 and 280 °C, the pressures varies between 15 and 51 bar in the experiment of Vanden Bussche and Froment [ 44 ].…”
Section: Reactor Model and System Descriptionmentioning
confidence: 99%
See 2 more Smart Citations